2009
DOI: 10.1091/mbc.e08-12-1161
|View full text |Cite
|
Sign up to set email alerts
|

Varp Is a Novel Rab32/38-binding Protein That Regulates Tyrp1 Trafficking in Melanocytes

Abstract: Two small GTPase Rabs, Rab32 and Rab38, have recently been proposed to regulate trafficking of melanogenic enzymes to melanosomes in mammalian epidermal melanocytes; however, the exact molecular mechanism of Rab32/38-mediated transport of melanogenic enzymes has never been clarified, because no Rab32/38-specific effector has ever been identified. In this study, we screened for a Rab32/38-specific effector by a yeast two-hybrid assay using a guanosine triphosphate (GTP)-locked Rab32/38 as bait and found that VP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(189 citation statements)
references
References 40 publications
7
182
0
Order By: Relevance
“…We previously thought that the ANKR domain of centaurin-␤2 was necessary and sufficient for Rab35 binding activity, the same as the ANKR1 domain of VPS9-ankyrin repeat protein that alone recognizes Rab32/38 (32), but the results of our deletion analysis indicated that an N-terminal flanking region and a C-terminal flanking region (AA580 -630 and AA730 -755, respectively) of the ANKR domain are also required for high affinity Rab35 binding activity (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously thought that the ANKR domain of centaurin-␤2 was necessary and sufficient for Rab35 binding activity, the same as the ANKR1 domain of VPS9-ankyrin repeat protein that alone recognizes Rab32/38 (32), but the results of our deletion analysis indicated that an N-terminal flanking region and a C-terminal flanking region (AA580 -630 and AA730 -755, respectively) of the ANKR domain are also required for high affinity Rab35 binding activity (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast Two-hybrid Assays-Yeast two-hybrid assays were performed by using pGBD-C1-Rab35(Q67L, Q67L/T76S/T81A, or Q67L/S5A) lacking the C-terminal geranylgeranylation site and pGAD-C1-RUSC2-RUN (12), pAct2-MICAL-1, pAct2-MICAL-cl, pAct2-MICAL-L1, pAct2-OCRL (7), pAct2-Fascin1, or pAct2-Cent␤2-ANKR (8) or by using pGBD-C1-Rab35(Q67L or S22N)⌬Cys (hereafter simply designated as QL or SN) and pAct2-Cent␤2-ANKR(WT or its mutants), pAct2-Cent␤1-ANKR, or pAct2-Cent␤5-ANKR as described previously (8,32). The yeast strain, medium, culture conditions, and transformation protocol used were as described previously (28).…”
Section: Co-immunoprecipitation Assays In Cos-7 Cells Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Rabex-5 to dendrite outgrowth and axon morphogenesis and Rab17 to dendrite morphogenesis) suggests that Rabex-5 activates other Rab family proteins besides Rab17 during the course of neurite morphogenesis. To pursue this possibility, we performed yeast two-hybrid assays with a panel of 60 different CA (GTP-locked) and CN (GDP-locked) Rabs to identify additional target Rabs of Rabex-5 (36). The results of the Rab-family-wide analysis showed that Rabex-5 specifically interacted with the CN forms of Rab5A/B/C, Rab17, and Rab21 (Fig.…”
Section: Rabex-5 Is Also Required For the Neuritic Localization Of Ramentioning
confidence: 99%